2019
DOI: 10.1096/fj.201801595rr
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of interleukin‐9 ameliorates experimental stroke by repairing the blood–brain barrierviadown‐regulation of astrocyte‐derived vascular endothelial growth factor‐A

Abstract: Astrocytes mediate the destruction of the blood–brain barrier (BBB) during ischemic stroke (IS). IL‐9 is a pleiotropic cytokine that we previously found to be highly expressed in peripheral blood mononuclear cells from patients with IS, and the presence of IL‐9 receptors on astrocytes has been reported in the literature. Here, we detected the effect of IL‐9 on astrocytes using an anti–IL‐9‐neutralizing antibody to treat rats with experimental stroke. Supernatants from astrocytes treated with or without oxygen–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Reactive astrocytes, characterized by proliferation and astrogliosis [defined by GFAP upregulation ( Zamanian et al , 2012 ; Hol and Pekny, 2015 )], promote infarct progression ( Yao et al , 2015 ), exacerbate inflammation ( Colombo and Farina, 2016 ), compromise BBB function ( Tan et al , 2019 ) and aggravate cytotoxic oedema ( Manley et al , 2000 ; Liu and Chopp, 2016 ). No GFAP signal was detected in the lesion area itself probably because of astrocyte necrosis in the core of ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive astrocytes, characterized by proliferation and astrogliosis [defined by GFAP upregulation ( Zamanian et al , 2012 ; Hol and Pekny, 2015 )], promote infarct progression ( Yao et al , 2015 ), exacerbate inflammation ( Colombo and Farina, 2016 ), compromise BBB function ( Tan et al , 2019 ) and aggravate cytotoxic oedema ( Manley et al , 2000 ; Liu and Chopp, 2016 ). No GFAP signal was detected in the lesion area itself probably because of astrocyte necrosis in the core of ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Lots of bacterial and viral infections cause degradation or disorganization of TJs indirectly through diverse pathways 71‐73 . For example, cytokines including IL‐1β, IL‐6, IL‐9, IL‐17, IFN‐γ, TNF‐α, and CCL2, can lead to reduced TJ expression or false TJ allocation 74‐79 . Claudin‐5 among others is the most important TJ protein responsible for selective permeability of the BBB, and inflammation leads to its downregulation and BBB disruption 80 .…”
Section: Mechanisms Of Peripheral Inflammation‐induced Bbb Disruptionmentioning
confidence: 99%
“…It has been reported that during inflammation astrocytes altered claudin‐5 expression likely by upregulating the immune‐related GTPase family M‐1 protein (IRGM‐1) in the EAE mouse model 99 . In middle cerebral artery occlusion (MCAO) model, researchers found high IL‐9 expression in peripheral blood and IL‐9 receptors on astrocytes, and further study revealed that IL‐9 enhances the permeability of the BBB by promoting the secretion of VEGF‐A from astrocytes 76 . Peripheral inflammation induced by LPS can cause proliferation and activation of astrocytes, changes in the end‐feet structure and altered expression of other related gene, which collectively and indirectly lead to destruction of the BBB 100,101 …”
Section: Mechanisms Of Peripheral Inflammation‐induced Bbb Disruptionmentioning
confidence: 99%
“…Recently, Bonsack et al [29] demonstrated the importance of astrocyte-derived pentraxin-3 in regulating BBB permeability. Tan et al [30] have also shown that leukocytes can cause BBB disruption in stroke via effects on astrocytes. Leukocytes release interleukin-9 that causes astrocytes to release vascular endothelial growth factor-A which, in turn, causes BBB hyperpermeability.…”
Section: Crosstalk and Cellular Signaling Within The Nvumentioning
confidence: 99%